2013
DOI: 10.22458/urj.v5i1.199
|View full text |Cite
|
Sign up to set email alerts
|

Performance of selected macroinvertebrate-based biotic indices for rivers draining the Merendon Mountains region of Honduras

Abstract: Cusuco National Park, a cloud forest park situated in the Merendon Mountains region of Honduras, is home to considerable biodiversity with a very high degree of endemism. Like many other cloud forest parks in Central America, it was declared a protected area not because of its biodiversity, but mainly because of its function in protecting river water quality in the headwaters draining the park. Illegal and authorised forest clearance for agricultural activity such as coffee production and pasture for animals a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The present analysis resulted in 53 collected families (Table 3). This number compares well with the number of families collected by Lorion and Kennedy [27] and O'Callaghan and Kelly-Quinn [58] in Costa Rican and Honduran neotropical rivers, who reported 56 and 60 families, respectively. The present study also identified a total of 98 genera (Table 3).…”
Section: Diversity and Composition Of Macroinvertebrate Assemblagessupporting
confidence: 84%
See 2 more Smart Citations
“…The present analysis resulted in 53 collected families (Table 3). This number compares well with the number of families collected by Lorion and Kennedy [27] and O'Callaghan and Kelly-Quinn [58] in Costa Rican and Honduran neotropical rivers, who reported 56 and 60 families, respectively. The present study also identified a total of 98 genera (Table 3).…”
Section: Diversity and Composition Of Macroinvertebrate Assemblagessupporting
confidence: 84%
“…These studies usually have found this index to be satisfactory for reflecting water quality [10, Agrorural Ecosystem Effects on the Macroinvertebrate Assemblages of a Tropical River 25 http://dx.doi.org/ 10.5772/59073 12,22,[60][61][62][63], especially the Costa Rican adaptation [58]. Sánchez Argüello et al [61] undertook in their Panamanian study a comparison between the Colombian and Costa Rican adaptations of the BMWP index and found the latter to be more unforgiving in its water quality evaluation.…”
Section: Biodiversity In Ecosystems -Linking Structure and Function 24mentioning
confidence: 99%
See 1 more Smart Citation
“…The development and implementation of effective biological methods for assessing water quality of lotic ecosystems in Honduras, and generally in Central America, is a topic of major importance, considering the growing environmental alteration that affects this region [25,26]. However, to our knowledge, only a few studies have been performed to date [9,[27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of lotic system health is particularly important in developing tropical countries, where population and economic growth are threatening the exceptional regional biodiversity. Recently, many studies have underlined that biological biomonitoring methods may offer interesting possibilities of application in Neotropical streams [8,9]; may overcome logistic difficulties associated with traditional chemical-physical surveys; and appear advantageous from an economic point of view, providing synthetic information in a rapid way [10]. Besides, the collection and analysis of biological indicators, such as benthic macroinvertebrates, requires moderate training, especially when organisms are identified by family.…”
Section: Introductionmentioning
confidence: 99%